What influences intention to purchase sustainable products? impact of advertising and materialism. Issue 8 (29th June 2020) - Mandliya, Anshul; Varyani, Vartika; Hassan, Yusuf; Akhouri, Anuja; Pandey, Jatin
Abstract : Purpose: The purpose of the present study is to examine the relationship between Social and Environmental Accountability (SEA), Attitude towards Environmental Advertising (AEA), Materialism, and Intention to purchase Environmentally Sustainable Products (IPESP). Design/methodology/approach: The study sample consists of 205 business students from two B schools in India. Data was collected through the survey method, and the moderated-mediation model was statistically tested using SPSS Process Macro software. Findings: The findings of the study suggest that the attitude towards social and environmental accountability (SEA) is positively associated with the intention to purchase environmentally sustainable products (IPESP). Moreover, this relationship is mediated and moderated by AEA and materialism, respectively. Practical implications: The findings of the study reveal that a consumer with low materialism and a positive attitude for both environmental sustainability and environmental advertising has higher chances of purchasing environmentally sustainable products. Originality/value: This study contributes to the existing literature on sustainability by providing a basis for understanding the moderated-mediation mechanism, which affects the relationship between SEA and IPESP; two key variables that have not been examined in combination.